An Operation for Developing Scientific Process Skills by using the Scientific Activities for Prathom Suksa Six (Grade Six) Students of Nonjik School under Ubon Ratchathani’s Primary Educational Service Area 5 - เชื้อพงษ์ สายทอง; ประทุมเวียง ชูชีพ; เอกะกุล ธีรวุฒิ (Ubon Ratchathani Journal of Research and Evaluation, 2021)
The research aimed to develop the scientific process skills by using the science show and to study achievement before and after the operation. The samples were 19 Prathom Suksa six students of Ban Nonjik School. The important research instrument was achievement test. The research was the action research based on technique of Kemmis and McTaggart. The technique had four stages in each of three operation cycles. The datas were collected by observation, interviewing and testing. Statistics used in data analysis were percentage, mean, standard deviation and content analysis for qualitative datas. The research findings were as follows. The students had higher scientific process skills. Additionally, the teacher’s personality was important for managing positive classroom climate. The instructional model could become more effective in developing the desired skills on the students’ part. The students had an achievement of 52.98 percent on the science process before learning. They had 84.74% achievement on average after learning which was higher than the set criterion 70 percent. All students had passed the criterion 100 percent.